Impact of Intermediate Hyperglycemia and Diabetes on Immune Dysfunction in Tuberculosis. (13th June 2020) - Eckold, Clare; Kumar, Vinod; Weiner, January; Alisjahbana, Bachti; Riza, Anca-Lelia; Ronacher, Katharina; Coronel, Jorge; Kerry-Barnard, Sarah; Malherbe, Stephanus T; Kleynhans, Leanie; Stanley, Kim; Ruslami, Rovina; et al.
Abstract: Background: People with diabetes have an increased risk of developing active tuberculosis (TB) and are more likely to have poor TB-treatment outcomes, which may impact on control of TB as the prevalence of diabetes is increasing worldwide. Blood transcriptomes are altered in patients with active TB relative to healthy individuals. The effects of diabetes and intermediate hyperglycemia (IH) on this transcriptomic signature were investigated to enhance understanding of immunological susceptibility in diabetes-TB comorbidity. Methods: Whole blood samples were collected from active TB patients with diabetes (glycated hemoglobin [HbA1c] ≥6.5%) or IH (HbA1c = 5.7% to <6.5%), TB-only patients, and healthy controls in 4 countries: South Africa, Romania, Indonesia, and Peru. Differential blood gene expression was determined by RNA-seq (n = 249). Results: Diabetes increased the magnitude of gene expression change in the host transcriptome in TB, notably showing an increase in genes associated with innate inflammatory and decrease in adaptive immune responses. Strikingly, patients with IH and TB exhibited blood transcriptomes much more similar to patients with diabetes-TB than to patients with only TB. Both diabetes-TB and IH-TB patients had a decreased type I interferon response relative to TB-only patients. Conclusions: Comorbidity in individuals with both TB and diabetes is associated with altered transcriptomes, with an expected enhanced inflammation in the presence of both conditions, but also reduced type I interferon responses in comorbid patients, suggesting an unexpected uncoupling of the TB transcriptome phenotype. These immunological dysfunctions are also present in individuals with IH, showing that altered immunity to TB may also be present in this group. The TB disease outcomes in individuals with IH diagnosed with TB should be investigated further. Abstract : Our study shows that people with diabetes and tuberculosis have altered peripheral immune profiles compared to people with only tuberculosis, and that these differences also exist in patients with intermediate hyperglycemia.